Hotels in the City of Algiers During the Ottoman Era: A Historical and Statistical Study Based on Sources - triki, salim; nafti, Ouafia (The Algerian Historical Journal, 2026)
The study aims to trace the history of the beginnings of hotel construction in the city of Algiers during the Ottoman era, attempting to enumerate and locate their spread, with a focus on their role in the flourishing of trade. The study also seeks to highlight the role of hotels in the economic and social life of the city during that period. One of the most important findings is that hotels played a vital role in supporting trade in the city by providing services to merchants and travelers. However, providing an accurate count of the number of hotels in Algiers during the Ottoman era may be difficult due to the lack of detailed information in historical documents and sources, especially since many hotels in Algiers were demolished, particularly in the lower part of the city.